2023
DOI: 10.4269/ajtmh.22-0734
|View full text |Cite
|
Sign up to set email alerts
|

Food as a Driver of a Cholera Epidemic in Jijiga, Ethiopia—June 2017

Abstract: We conducted a case-control study to identify risk and protective factors during a cholera outbreak in Jijiga, Ethiopia, in June 2017. A case-patient was defined as anyone > 5 years old with at least three loose stools in 24 hours who was admitted to a cholera treatment center in Jijiga on or after June 16, 2017. Two controls were matched to each case by type of residency (rural or urban) and age group. We enrolled 55 case-patients and 102 controls from June 16 to June 23, 2017. Identified risk factors for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In a recent study of a cholera outbreak in Jigjiga, people had a higher risk of cholera infection if they consumed unrefrigerated food, dined in commercial restaurants or purchased food from street vendors. 57 A study on the outbreak of cholera in Addis Ababa found the consumption of raw vegetables to be a risk factor for cholera infection. 55 Food service workers mostly report good knowledge of safe food handling and hygiene practices, but they lack adequate water, sanitation and hygiene infrastructure.…”
Section: Lack Of Food Safety Infrastructure Regulation and Enforcementmentioning
confidence: 99%
“…In a recent study of a cholera outbreak in Jigjiga, people had a higher risk of cholera infection if they consumed unrefrigerated food, dined in commercial restaurants or purchased food from street vendors. 57 A study on the outbreak of cholera in Addis Ababa found the consumption of raw vegetables to be a risk factor for cholera infection. 55 Food service workers mostly report good knowledge of safe food handling and hygiene practices, but they lack adequate water, sanitation and hygiene infrastructure.…”
Section: Lack Of Food Safety Infrastructure Regulation and Enforcementmentioning
confidence: 99%